PENERAPAN QRIS SEBAGAI ALAT PENGENDALIAN PENJUALAN DAN KEUANGAN PADA UMKM MIE BAKSO SI BOY - Sarah Desiree Lumban Gaol; Grace Orlyn Sitompul; Fanya Graceyla Siringoringo; Rocky Pradana Tarigan; Vern Marchella Palar (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This community service research aims to facilitate the use of the Quick Response Code Indonesian Standard (QRIS) as a tool for controlling sales and finances of the micro, small, and medium enterprise (MSME) Mie Bakso Si Boy. The main issue faced is the transaction recording system, which is still done manually. This can lead to recording errors, ambiguity, and difficulties in monitoring cash flow in real-time. Needs analysis, interviews, and observations were used, as well as socialization and training to implement and evaluate QRIS. The results of the activities showed that the use of QRIS can accelerate payments and improve financial recording more accurately and systematically. In addition, QRIS increases customer satisfaction and distinguishes business finances from personal ones. Thus, QRIS not only serves as a digital payment tool but also functions as a control and management tool that helps MSMEs become more competitive.